2002
DOI: 10.1007/s00421-002-0645-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of endurance capacity of quadriceps muscles in humans using surface electromyogram spectrum analysis during submaximal voluntary isometric contractions

Abstract: The measurement of endurance time ( t(lim)) is the procedure commonly used to quantify the ability of a muscle to maintain force. The relationship between surface electromyographic (sEMG) manifestations of localised muscle fatigue and t(lim) during an effort at 50% of maximal voluntary isometric torque of the knee extensors (vastus lateralis and vastus medialis) until exhaustion was studied in 14 healthy volunteers. It was carried out to test whether changes in sEMG computed over shorter periods than expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 58 publications
6
39
0
Order By: Relevance
“…46 Estimates of MFCV were accepted only when cross-correlation values were higher than 0.7, which has been reported to be an acceptable correlation coefficient for VL, due to the fibers' orientation. 34,43 In order to obtain acceptable time resolution, the time delay was computed with a resolution of 10 to 20 s, 36 which was obtained by interpolating the cross-correlation function near the maximum with a sinc function.…”
mentioning
confidence: 99%
“…46 Estimates of MFCV were accepted only when cross-correlation values were higher than 0.7, which has been reported to be an acceptable correlation coefficient for VL, due to the fibers' orientation. 34,43 In order to obtain acceptable time resolution, the time delay was computed with a resolution of 10 to 20 s, 36 which was obtained by interpolating the cross-correlation function near the maximum with a sinc function.…”
mentioning
confidence: 99%
“…This calculation time period (i.e., 50% T lim ), therefore, represents a threshold that should not be exceeded for a T lim prediction to remain useful. It also appears that results from spectral parameters of the sEMG signal recorded from the most fatigable muscle established the most reliable relationships between sEMG signal and T lim , and subsequently a better prediction of T lim (Badier et al 1993;Dolan et al 1995;Maisetti et al 2002a;Mannion and Dolan 1996;van Dieen et al 1998;van Dieen et al 1993). However, during a complex multijoint and bilateral task, we have indicated that T lim prediction was not reliable, probably because of the great number of muscles and joints involved (Boyas et al 2009;Maisetti et al 2006).…”
Section: Introductionmentioning
confidence: 76%
“…(A ? B) is the sum of both areas beneath and above the sEMG parameter-time course delimited by a signal reference value corresponding to the mean value of the sEMG parameter computed over the first 2 s of the test [for further information, see (Maisetti et al 2002a)]. This variable is a dimensionless and regression-free fatigue index that can be applied to any data pattern without previous assumptions.…”
Section: Signal Analysis and Processingmentioning
confidence: 99%
See 2 more Smart Citations